An Unknown King in an Unknown City - Lambert, W.G. (Fs Tadmor)
an Inscription of Aššur-ketti-l?šir, king of (the land of) A-a; probably Middle Assyrian; belongs to the collection of the Lands of the Bible Archaeological Foundation; hand copy on p.319; vgl. dazu St.M. Maul in KeiBi 52